2019
DOI: 10.32674/jump.v3i1.1077
|View full text |Cite
|
Sign up to set email alerts
|

From Studentship to Academia

Abstract: At all levels of education in the Science, Technology, Engineering, and Mathematics (STEM) disciplinary fields, there are disparities in participation according to gender. This study explores the educational and professional experiences of female faculty in STEM in universities in Ghana. In-depth semi-structured interviews were undertaken employing 20 participants from universities in Ghana. Findings indicate that despite their success fueled by the support system available to them, gender disparities, fostere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Awan et al (2017) concurred that interest in STEM-related subjects influences students to pursue further studies in STEM. Similar findings were revealed by Boateng and Gaulee (2019) and Wang (2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Awan et al (2017) concurred that interest in STEM-related subjects influences students to pursue further studies in STEM. Similar findings were revealed by Boateng and Gaulee (2019) and Wang (2013).…”
Section: Discussionsupporting
confidence: 90%
“…Pupils who had preferences for programmes they were admitted to, made decisions often based on gender-traditional choices, with more females than males being motivated by their parents and peers in taking such decisions (Mastekaasa and Smeby, 2008). For instance, the traditional belief that boys are more competent in mathematics than girls usually results in more boys enrolling in mathematics-related subjects (Boateng and Gaulee, 2019). Report by the Global Education Monitoring Team (2018) has also noted that women in Ghana account for less than one-quarter of all Science, Technology, Engineering, and Mathematics (STEM) degrees.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though research show that professions related to mathematics and science are perceived as male-dominated occupations, mathematics in STEM content mostly shows that it has the strongest masculinity for both genders, followed by physics and chemistry (Makarova et al, 2019). In the study of Boateng & Gaulee (2019), the interviews conducted with female faculty members specialized in STEM fields in universities in Ghana that revealed that despite the supports accessible to them, the gender differences perpetuated by patriarchy characterized these women's educational and professional experiences notwithstanding their achievement. Their gendered experiences in higher education were worsened by the fact that certain sources of support turned out to be sources of prejudice.…”
Section: Introductionmentioning
confidence: 98%